Faktor-Faktor Yang Mempengaruhi Keberhasilan Asi Eksklusif 6 Bulan Pada Ibu Yang Memiliki Bayi Usia 6-12 Bulan Di Desa Kemantren Kecamatan Jabung Kabupaten Malang - sariati, yuseva; Prastyaningrum, Verra Yuni; Kurniasari, Putri; Melly, Mustarina (Journal of Issues in Midwifery, 2017)
ABSTRACTExclusive breastfeeding is breastfeeding for 6 months without any additional foods or drinks others. Based on reports Nutrition Ditjen and Kemenkes RI 2014, exclusive breastfeeding in Indonesia was still low (52.3%) and in the East Java provincial 74.0%, it has not reached yet from the target 80%. The purpose of this research is to analyze the factors that influence the success of exclusive breastfeeding to 6 months at mothers who have 6-12 months aged babies in the Kemantren village Jabung District of Malang. Observational cross sectional research conducted to 63 respondents whom choosen by purposive sampling methode. Data collected by quistionnaire that measure family support, maternal employment status, maternal education, and mother’s knowledge of breast milk’s level. The obtained data were analyzed by using Chi-Square. The results of this study showed most of the mother got enough support from family (57.1%), and mother’s knowledge of breast milk’s level have been good (54,0%). The variable had effect on exclusive breastfeeding was mother’s knowlegde of breast milk’s level (p=0,005). The variables who had no effect on exclusive breastfeeding were family support (p=0,051), maternal employment status (p=0,263), and maternal education level (p=0,145). The conclusion of this study is the mother’s knowledge of breast milk level has effects on exclusive breastfeeding so must to do promotion to the mothers before pregnancy and her families about the importance of breastfeeding.